Biomass gasification for hydrogen rich gas in a decoupled triple bed gasifier with olivine and NiO/olivine. (January 2019) - Tursun, Yalkunjan; Xu, Shaoping; Abulikemu, Abulizi; Dilinuer, Talifu
Highlights: Decoupled triple bed gasification (DTBG) system has potential for in situ tar removal. The tar content decreased to <1 g/Nm 3 with NiO/olivine catalyst. Properties of olivine and NiO/olivine during the redox cycle were investigated. Abstract: Catalytic steam gasification of biomass has been carried out in decoupled triple bed gasification (DTBG) system which consists of pyrolyzer, reformer and combustor. Olivine and NiO/olivine used as in-situ tar destruction catalyst. The result shows the gasification system with catalytic bed materials allows an option to improve tar removal that enhances H2 production. A gas yield of 1.59 Nm 3 /kg daf with H2 concentration of 56.1 vol% and tar content as low as 0.6 g/Nm 3 has been achieved with the presence of NiO/olivine. Olivine and NiO/olivine reduced tar yield by 55% and 94% respectively compared to quartz. Gas yield, tar removal efficiency and water conversion enhanced by higher reformer temperature. The longer residences time of catalyst in reformer leads in-situ reduction of olivine and NiO/olivine that adds up in-situ tar reforming. Particularly, in-situ reduction of NiO to metallic Ni enhances tar and CH4 reforming reaction.